Black Esophagus and Diabetic Ketoacidosis - Anumeet S. Tuli; Japjot Grewal; Mohammad Alqaisieh; Stefan Canacevic; Grigoriy E. Gurvits (Annals of Internal Medicine: Clinical Cases)
Black esophagus, also known as acute esophageal necrosis and Gurvits syndrome, is a rare medical condition characterized by a striking endoscopic appearance of diffuse black discoloration of the esophageal mucosa almost universally affecting the distal esophagus and extending proximally at various lengths. Risk factors include male sex, advanced age, cardiovascular and renal disease, diabetic ketoacidosis, thromboembolic disease, malignancy, and general debilitation. Endoscopic findings are classic and tissue histology is not required for diagnosis. Acute esophageal necrosis carries a poor prognosis, with up to one third of patients succumbing to underlying comorbid conditions.